1927
DOI: 10.1084/jem.45.5.849
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Poisoning in Mammals

Abstract: 1. Oxygen in concentrations of over 70 per cent of an atmosphere is poisonous to dogs, rabbits, guinea pigs and mice. 2. The poisonous effects manifest themselves in drowsiness, anorexia, loss of weight, increasing dyspnea, cyanosis and death from oxygen want. 3. The cause of oxygen want is a destructive lesion of the lungs. 4. The lesion may be characterized grossly as an hemorrhagic edema. Microscopically there is to be seen in varying degrees of intensity (a) cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1928
1928
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 8 publications
1
18
0
1
Order By: Relevance
“…This became known as the Haber-Weiss reaction and is now believed to be at the core of much ROS generation in cells. However, the connection between oxygen toxicity and ROS generation was not then understood (27). Using electron spin resonance, Commoner et al (67) published the first direct evidence that free radicals were produced in living cells and found that free radical levels were higher in tissues that were more metabolically active.…”
Section: A Mitochondrial Free Radical Productionmentioning
confidence: 99%
“…This became known as the Haber-Weiss reaction and is now believed to be at the core of much ROS generation in cells. However, the connection between oxygen toxicity and ROS generation was not then understood (27). Using electron spin resonance, Commoner et al (67) published the first direct evidence that free radicals were produced in living cells and found that free radical levels were higher in tissues that were more metabolically active.…”
Section: A Mitochondrial Free Radical Productionmentioning
confidence: 99%
“…Barach has reported that pulmonary edema invariably develops in rabbits given oxygen in concentrations of 80 per cent or more (23). Binger also observed pneumonia in dogs, rabbits, and guinea pigs exposed to 80 per cent oxygen; the first symptoms of respiratory distress appeared in 2 to 5 days (24). Paine chamber the air supply of which contained 90 per cent oxygen.…”
Section: Concentrations Of Alveolar Oxygen Obtained;mentioning
confidence: 93%
“…Toxicity to oxygen has been reported in rabbits, featuring widespread pulmonary lesions (4). For this reason, the heart and lungs were examined in 9 of the rabbits receiving oxygen, in 2 of the rabbits receiving cortisone, and in 12 of the control series.…”
Section: Methodsmentioning
confidence: 99%